Intervention in gut microbiota increases intestinal γ-aminobutyric acid and alleviates anxiety behavior: a possible mechanism via the action on intestinal epithelial cells - Ikegami, Mion; Narabayashi, Hikari; Nakata, Kazuaki; Yamashita, Miyu; Sugi, Yutaka; Fuji, Yushiro; Matsufuji, Hiroshi; Harata, Gaku; Yoda, Kazutoyo; Miyazawa, Kenji; Nakanishi, Yusuke; Takahashi, Kyoko (Frontiers in Cellular and Infection Microbiology, 2024)
The role of the gut microbiota in the gut-brain axis has attracted attention in recent years. Some gut microbiota produces γ-aminobutyric acid (GABA), a major inhibitory neurotransmitter in mammals, in vitro, but the correlation between gut microbiota composition and intestinal GABA concentration, as well as the action of intestinal GABA in vivo, are poorly understood. Herein, we found that the intestinal GABA concentration was increased in mice by the intervention of the gut microbiota with neomycin or Bifidobacterium bifidum TMC3115 (TMC3115). Administration of TMC3115 reduced anxiety without affecting serum levels of serotonin, corticosterone, or GABA. We further found that intestinal epithelial cells expressed GABA receptor subunits and mediated mitogen-activated protein kinase signaling upon GABA stimulation. In addition, administration of TMC3115 induced mitogen-activated protein kinase signaling in colonic epithelial cells but not in small intestinal epithelial cells in mice. These results indicate that GABA produced by the gut microbiota, mainly in the colon, may affect host behavioral characteristics via GABA receptors expressed in intestinal epithelial cells without being transferred to the blood. This study suggests a novel mechanism by which intestinal GABA exerts physiological effects, even in the presence of the blood-brain barrier.